Macronutrient accumulation in green pepper (Capsicum annuum L.) as affected by different production technologies - Terbe, I.; Szabó, Zs.; Kappel, N. (International Journal of Horticultural Science, 2006)
Based on the experiments, an assessment was made to determine for green pepper the amount of nutrients extracted by unit weight of fruit and plant parts not meant to be consumed (foliage, stem, root), i.e. the specific nutrient requirements of pepper. A further objective was to find out to what extent nutrient accumulation in individual plant organs was influenced by differences in production technology and soil conditions.